Strengths-Weaknesses-Opportunities-Threats (SWOT) Analysis of Conservation Agriculture - Chatterjee, Dibyendu (Indian Journal of Hill Farming, 2016)
Conservation agriculture is an option that attempt to achieve profits with high and sustained production levels while conserving the natural resources and environment. It is based on three principles viz. permanent soil cover, minimum soil disturbance and crop rotations. Maintaining a soil cover is necessary to protect the soil physically from sunlight, rain and wind and to feed soil biota. Conservation tillage can reduce erosion, increase organic matter content and improve physical, chemical and biological properties of soil. Soil surface can be covered either by mulch or by cover crops. Crop rotation is also essential to offer a diverse food to the soil microorganisms and to increase farm incomes. Conservation agriculture proved beneficial on long term basis in many ways, viz. reduction in cost of production, decreasing energy input, saving of nutrients and increased yields. However, problem like short term yield decline, weed infestation etc. under conservation agriculture have also been reported in India. There is need to discuss critically different aspects of this alternative management approach so as to find out its feasibility under Indian conditions.